O8 Tracking wound infection with smartphone technology (twist): a randomised controlled trial in emergency surgery patients. (30th July 2021) - McLean, K A; Mountain, K E; Shaw, C A; Drake, T M; Ots, Riinu; Knight, Stephen R; Fairfield, Cameron J; Sgrò, Alessandro; Skipworth, Richard J E; Wigmore, Stephen J; Potter, Mark A; Harrison, Ewen M; et al.
Abstract: Introduction: Surgical site infections (SSI) complicate 2%–10% of general surgery cases, and represent a significant burden on acute healthcare services. We aim to investigate if a smartphone-delivered wound assessment tool results in earlier treatment. Method: This parallel, single-blinded randomised control trial enrolled adult emergency abdominal surgery patients in two tertiary hospitals (ClinicalTrials.gov number, NCT02704897). Patients were randomised (1:1 ratio) between standard postoperative care and additional access to a smartphone-delivered wound assessment tool for 30-days postoperatively. Patients routinely submitted wound questionnaires and photos for surgical review at postoperative days 3, 7, and 15. The primary outcome measure was time-to-diagnosis of SSI (CDC definition) within 30 postoperative days. Result: 492 patients undergoing emergency surgery were randomised (smartphone intervention = 223; standard care = 269). There was no significant difference ( P = 0.513) in the 30-day SSI rate between trial arms: 21 (9.4%) in smartphone vs 20 (7.4%) in standard care. While the mean time-to-diagnosis of SSI was 9.3 days (SD = 6.3) in the smartphone group, and 11.8 days (SD = 6.7) in the control group, this did not demonstrate a significant difference for the primary outcome ( P = 0.255). However, patients in the smartphone group had 3.7-fold higher odds to be diagnosed in first 7 postoperative days (95% CI: 1.02 to 13.51, P = 0.043). Conclusion: Digital patient-driven postoperative wound follow-up can be feasibly delivered in a broad cohort of emergency surgery patients. This can facilitate triage of patients to the appropriate level of assessment required, allowing diagnosis of SSI earlier in the postoperative period. Take-home Message: Digital patient-driven postoperative wound follow-up can be feasibly delivered in a broad cohort of emergency surgery patients. This can facilitate triage of patients to the appropriate level of assessment required, allowing diagnosis of SSI earlier in the postoperative period.